Antimicrobial Activity of Selected Probiotic Bacteria Isolated from Sudanese Traditional Dairy Product "Rob" - Salih, Aymen M. Mohammed; Hassan, Zolfgar Ramdan; El Sanousi, Sulieman Mohamed (Pakistan Journal of Nutrition, 2011)
This study was carried out to evaluate the antibacterial activity of selected probiotic strains isolated from the Sudanese traditional fermented dairy food ‘Rob’. Twenty seven samples of Rob were used in this study. The strains were identified by using morphological, physiological and biochemical methods. The isolates of Lactic Acid Bacteria (LAB) were identified as Lactococcus lactis, Lactobacillus delbrecukii and Enterococcus feacium. Cell-free supernatants (CFS) were obtained from the isolates and screened for their antibacterial activity. Pathogenic bacteria such as Bacillus subtilis, Staphylococcus aureus, Klebsiella pneumoniae, Salmonella typhi and E.coli were used as targets. The CFS inhibited the growth of a range of Gram-positive and Gram-negative microorganisms. This result indicated that these probiotic strains could be used as therapeutic agents.